Monocyte programming by cancer therapy - Patysheva, Marina; Frolova, Anastasia; Larionova, Irina; Afanas'ev, Sergey; Tarasova, Anna; Cherdyntseva, Nadezhda; Kzhyshkowska, Julia (Frontiers in immunology, 2022)
Monocytes in peripheral blood circulation are the precursor of essential cells that control tumor progression, that include tumor-associated macrophages (TAMs), dendritic cells (DCs) and myeloid-derive suppressor cells (MDSC). Monocytes-derived cells orchestrate immune reactions in tumor microenvironment that control disease outcome and efficiency of cancer therapy. Four major types of anti-cancer therapy, surgery, radiotherapy, chemotherapy, and most recent immunotherapy, affect tumor-associated macrophage (TAM) polarization and functions. TAMs can also decrease the efficiency of therapy in a tumor-specific way. Monocytes is a major source of TAMs, and are recruited to tumor mass from the blood circulation. However, the mechanisms of monocyte programming in circulation by different therapeutic onsets are only emerging. In our review, we present the state-of-the art about the effects of anti-cancer therapy on monocyte progenitors and their dedifferentiation, on the content of monocyte subpopulations and their transcriptional programs in the circulation, on their recruitment into tumor mass and their potential to give origin for TAMs in tumor-specific microenvironment. We have also summarized very limited available knowledge about genetics that can affect monocyte interaction with cancer therapy, and highlighted the perspectives for the therapeutic targeting of circulating monocytes in cancer patients. We summarized the knowledge about the mediators that affect monocytes fate in all four types of therapies, and we highlighted the perspectives for targeting monocytes to develop combined and minimally invasive anti-cancer therapeutic approaches.
Gesehen am 21.08.2023